2016
DOI: 10.1007/s10068-016-0101-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimum mixture of transglutaminase, l-ascorbic acid and xylanase for the quality and consumer acceptability of bread using response surface methodology

Abstract: The optimum levels of transglutaminase (TGase), l-ascorbic acid (l-AA), and xylanase (Xyl) were determined using response surface methodology to improve quality and consumer acceptability of bread made with wheat flour. A Box-Behnken design with three independent variables (TGase, l-AA, and Xyl) and three levels was used to develop models for the different responses (peak time, mixing tolerance, extensibility, resistance, specific volume, hardness, and consumer acceptability). Overall, l-AA and Xyl improved do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Interestingly, in a study evaluating combinations of transglutaminase, xylanase, and ascorbic acid in wheat breads, higher levels of transglutaminase resulted in better sensory scores, despite lowering bread volume and increasing bread hardness (Kim & Kim, 2016). Those authors used a principal component analysis, which suggested that their results may have been related to an inverse relationship between bread volume and bread moisture content, since dough water levels were kept constant for all enzyme treatments.…”
Section: Combined Use Of Improversmentioning
confidence: 99%
“…Interestingly, in a study evaluating combinations of transglutaminase, xylanase, and ascorbic acid in wheat breads, higher levels of transglutaminase resulted in better sensory scores, despite lowering bread volume and increasing bread hardness (Kim & Kim, 2016). Those authors used a principal component analysis, which suggested that their results may have been related to an inverse relationship between bread volume and bread moisture content, since dough water levels were kept constant for all enzyme treatments.…”
Section: Combined Use Of Improversmentioning
confidence: 99%
“…Wheat starch is the primary component of wheat endosperm and is known to influence the structure by providing a rigid network in baked products during gelatinization (5). The content of protein in wheat flour is different, depending on the types of baked products such as snacks, noodles, and breads, and it can be used as an indicator of wheat quality, especially in yeast-leavened products (6). Thus, starch and protein in flour have a major impact on wheat quality and its final products.…”
Section: Introductionmentioning
confidence: 99%